Sistem Appraisal terhadap Teks Berita Editorial Penerimaan Peserta Didik Baru (PPDB) 2019 - Adolfina Krisifu; Martha Betaubun (Journal of Education Papua Baru, 2023)
The zone system in the admission of new students (PPDB) is still a hotly debated issue. The objectives of this study are 1) to identify and classify words or phrases in sentences that contain appraisal on the attitude side which contains elements of affect, judgment, and appreciation; 2) to find words or phrases from the three types of attitude that have graduation; and 3) to provide a review of appraisal analysis from the point of view of editorial news writers in evaluating the zone system. This research method is descriptive qualitative with content analysis design. The findings were  a number of positive and negative statements based on appraised items by appraisers. Keywords: Critical discourse analysis, editorial news, appraisal system, zone system